Efektivitas Program Sosialisasi Keamanan Pangan Berdasarkan Skor Keamanan Pangan terhadap Peningkatan Pengetahuan Mahasiswa Pamulang - Awwalia Majida, Lia; Yulita, Refi; Yulia, Yulia (Ikatan Ahli Kesehatan Masyarakat Indonesia Kota Tangerang Selatan, 2024)
Data from the Ministry of Health over the past three years indicate a high number of food poisoning outbreaks. To address this, food safety knowledge among students must be improved by integrating food safety into university curricula, allowing students to help tackle foodborne illnesses. This study aims to evaluate the increase in food safety knowledge among public health students at Stikes X. The research uses a descriptive analytic approach with a cross-sectional design and an experimental method involving a one-group pre-test and post-test design. The population comprises 141 public health students from the 2022 cohort at Stikes X, aged 18-23, in Pamulang district, South Tangerang Regency. Systematic random sampling with inclusion and exclusion criteria was applied, resulting in a sample of 104 students. Data normality was tested using the Kolmogorov-Smirnov test, and the Wilcoxon test was used for data analysis. The results show a significant difference between pre-test and post-test scores after the food safety socialization program, with a mean score increase of 14.59 and a p-value of 0.000 (p<0.05). The program effectively enhanced students' food safety knowledge. Future research should include more locations for more representative results